2014
DOI: 10.1111/fwb.12372
|View full text |Cite
|
Sign up to set email alerts
|

Total phosphorus thresholds for regime shifts are nearly equal in subtropical and temperate shallow lakes with moderate depths and areas

Abstract: SUMMARY1. Published research suggests that the total phosphorus (TP) thresholds for the regime shifts between a clear-water state dominated by submersed macrophytes and a turbid-water state dominated by phytoplankton in shallow lakes vary with forms of lake basins and climates. However, such hypotheses remain untested by direct field evidence. We therefore tested the hypotheses with empirical data from subtropical lakes on the Yangtze floodplain and also from other lakes in temperate to tropical zones. 2. TP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 47 publications
4
51
0
Order By: Relevance
“…) suggested to entail high risk of macrophyte loss in Yangtze shallow lakes (Wang et al, 2014) and the level (0.018 mg L −1 ) suggested as a threshold for a dominance shift from macrophytes to phytoplankton in Canadian lakes (Bayley et al, 2007). The relatively minor effect of nitrogen may be due to a weak development of periphyton compared with other studies showing a strong positive effect of nitrogen on periphyton growth (Özkan et al, 2010) and an associated decline in macrophyte growth (Olsen et al, 2015;Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…) suggested to entail high risk of macrophyte loss in Yangtze shallow lakes (Wang et al, 2014) and the level (0.018 mg L −1 ) suggested as a threshold for a dominance shift from macrophytes to phytoplankton in Canadian lakes (Bayley et al, 2007). The relatively minor effect of nitrogen may be due to a weak development of periphyton compared with other studies showing a strong positive effect of nitrogen on periphyton growth (Özkan et al, 2010) and an associated decline in macrophyte growth (Olsen et al, 2015;Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…Worldwide, with the increasing eutrophication of shallow lakes, a decline in the abundance of submersed macrophytes has often been seen (Körner, 2002;Ibelings et al, 2007;Wang et al, 2014), producing substantially negative impacts on the ecosystem structure, functioning, and services of shallow lakes (Scheffer, 1998;Jeppesen et al, 1998). Most scientists agree that phytoplankton shading promoted by increasing inputs of phosphorus is an underlying cause of the decreasing abundance, but the role of nitrogen has received increasing attention in recent years (Moss, 2001;Jeppesen et al, 2007;Moss et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the decline of submerged macrophytes continually happens in many eutrophic lakes throughout the world as a result of eutrophication with increasing nutrients [6,7]. It is well known that phosphorus (P) is often considered to be the most crucial growth limiting factor for plants in lakes [8,9], but the role of nitrogen (N) in submerged macrophytes recession has recently received increasing attention [10].…”
Section: Introductionmentioning
confidence: 99%
“…Dolman (2014) argued that our recent finding (Wang et al, 2014) of no marked effect of submerged macrophytes on the chlorophyll a (Chl a) to total phosphorus (TP) relationship in Yangtze subtropical lakes may not necessarily be valid due to the statistical procedure used to analyse the relationship between these two variables. 2.…”
mentioning
confidence: 99%
“…argued that the apparent weak effect of macrophytes on relationship of phytoplankton chlorophyll a (Chl a) to total phosphorus (TP) in Yangtze subtropical lakes reported by Wang et al (2014) was actually due to a mistake in testing the difference in the heights of the lines (intercepts) at a point with low TP of 1 lg L À1 . Dolman (2014) further suggested that the features of fish communities suppressing macrophyteassociated zooplankton that cause a strong macrophyte effect in tropical lakes are absent in the Yangtze subtropical lakes.…”
mentioning
confidence: 99%